2013
DOI: 10.1063/1.4812587
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reactively sputtered molybdenum oxide films for solar cell application

Abstract: Molybdenum oxide (MoO3) thin films were prepared via Radio Frequency (RF) sputtering at different ambient composition and post-deposition annealing. The effects on the structural, optical, and surface properties of the deposited films were investigated. The ambient oxygen concentration O2/(O2 + Ar) was varied from 10% to 100% at 10 mTorr. Post deposition anneals were performed in Ar at 300–500 °C. The films were analyzed using glancing incidence x-ray diffraction (GIXRD), UV/Vis/NIR spectrophotometry, and x-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 37 publications
3
41
0
2
Order By: Relevance
“…Vacancy induced band gap states in MoO 3 have been utilized for sub-band gap transitions and enhancement of solar cell device performance. 10,19,21 Critical for operation, the stability of oxygen defects was found to be dependent on the method of reduction, due to differences in bonding dependent on position in the structure. 9 The bonding types were examined in the context of surface reconstruction in a theoretical study by Coquet et al on slab models.…”
Section: Figurementioning
confidence: 99%
“…Vacancy induced band gap states in MoO 3 have been utilized for sub-band gap transitions and enhancement of solar cell device performance. 10,19,21 Critical for operation, the stability of oxygen defects was found to be dependent on the method of reduction, due to differences in bonding dependent on position in the structure. 9 The bonding types were examined in the context of surface reconstruction in a theoretical study by Coquet et al on slab models.…”
Section: Figurementioning
confidence: 99%
“…For the MoO 3 ¢0.55H 2 O, the relatively sharp peaks at 974 and 905 cm ¡1 are likely due to the stretching of MoDO double bond. The peaks [26,27] revealing that band gap value of the obtained MoO 3 is reasonable and credible. The optical band gap energy has minimal changes when the treatment temperature is below 350 C, displaying a weak temperature dependence.…”
Section: Resultsmentioning
confidence: 57%
“…Many studies have been reported in which the transition metal oxides are employed in organic-based optoelectronic devices such as organic solar cells [18e20], organic light emitting diodes [21e24] and organic thin film transistors [25,26]. Molybdenum oxide can be regarded as a promising candidate for the transparent back contact component at tandem and superstrate devices due to its high transparency higher than 80 percent in the visible and near infrared spectral region and also its relatively wide band gap energies of 2.6e2.9 eV [27,28]. It is also an appropriate material for the primary back contact in CIGS thin film solar cells owing to its high work function (~5.7 eV) [29].…”
Section: Introductionmentioning
confidence: 99%